Factors Influencing Risky Sexual Behavior Among High School Students in South Jakarta in 2022 - Antaria, Abdullah (Universitas Aisyah Pringsewu, 2024)
Each year, there is a concerning rise in premarital sexual activity among adolescent females aged 20-24 years (Ningsih, 2022). This study investigates the complex factors influencing risky sexual behavior among high school students in South Jakarta in 2022. Existing literature identifies numerous determinants, including parental education, knowledge, attitudes, peer influence, media exposure, age, gender, residence, religion, education level, family structure, sex education, culture, economic status, and substance use (Puspasari Tafa, 2020; Etrawati et al., 2017).Using an ecological approach, the study comprehensively analyzes these factors across microsystem, mesosystem, and macrosystem levels to effectively address risky sexual behaviors among adolescents. A cross-sectional survey of 208 10th-grade students employed purposive sampling and structured questionnaires examining thirteen variables guided by Green's PRECEDE model. Findings indicate 43.3% of respondents engage in risky sexual behaviors, with significant associations found with age, knowledge, attitude, parental occupation, residence, vehicle ownership, relationship status, peer influence, parental role, religious adherence, and media impact (p 0.05). Religious adherence emerged as a predominant factor, with non-observant individuals being 200 times more likely to engage in risky sexual behaviors (p = 0.000, OR = 200.407).